(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fund Flow Statements summarize a firm’s inflow and outflow of funds. Simply put, it tells investors where funds have come from and where funds have gone. The statements are often used to determine whether companies efficiently source and utilize funds available to them. Fund flow statements are prepared by taking the balance sheets for two dates representing the coverage period. The increases and decreases must then be calculated for each item. Finally, the changes are classified under four categories: (1) Long-term sources, (2) long-term uses, (3) short-term sources, (4) short-term uses. It is also important to zero out the non-fund based adjustments in order to capture only the changes that are accompanies by flow of funds. However, income accrued but received and expenses incurred but not received reckoned in the profit and loss statement should not be excluded from the profit figure for the fund flow statement. Fund flow statements can be used to identify a variety of problems in the way a company operates. For example, companies that are using short-term money to finance long-term investments may run into liquidity problems in the future. Meanwhile, a company that is using long-term money to finance short-term investments may not be efficiently utilizing its capital